Romania - Functional Review : Labor and Social Protection Sector, Final Report, Volume 2 - World Bank (Washington, DC, 2013)
The Government of Romania (GOR), in agreement with the European Commission (EC), requested functional reviews of the Romanian public administration through an independent advisory service with the World Bank. The general objective of this advisory service is to review the current situation of the Labor and Social Protection (L&SP) sector, assess its functioning and develop an action plan that the GOR can use over the short- to medium-term to strengthen its effectiveness in the public administration. In meeting this objective, the World Bank examined: (i) whether the policy goals and objectives of the Ministry of Labor and Social Protection (MoLFSP) and its agencies are clearly defined in measurable and achievable terms; (ii) whether the management systems, policies, staffing, and organizational structure are appropriate for them to meet their objectives; and (iii) whether factors external to the institutions that may impede their ability to meet their objectives. The report is organized into two volumes. Volume One summarizes the main findings and messages, presents priorities for reform, and suggests an action plan to carry out these priority reforms. Volume Two provides chapters with the background diagnostics, assessment and findings in depth, covering: Main Sector Features and Institutional Mapping; Ministry of Labor Family and Social Protection; Labor Market; Pensions; Social Assistance (Cash Transfers); Social Assistance Services; Information Management (cross-cutting)